Os participantes da política pública de turismo do Pará a partir do modelo de fluxos múltiplos - 2007-2011 - NASCIMENTO, Vânia Lúcia Quadros (Universidade Federal do Pará, 2018)
This paper presents partial results of a research on tourism public policy in the Amazon. The research aims at identifying the active participants in the processes that influenced the formulation of Para state tourism public policy. It used as a theoretical reference the Multiple Streams Model of Kingdon. The empirical evidences were obtained from the document reviews about policies and their decision streams, as much as the semi-structured interviews with a public manager of tourism and the representative of the consulting firm; as well as the analysis of the minutes of the State Tourism Forum where the opinions of other participants in the decision making process are recorded. The results indicate that the alternatives for the development of tourism in this state have been materialized in the Plan “Ver-o-Pará”; that the active participants are also pointed out in it; that the performance of some actors that integrated Multiple Streams Model has not been identified; and that the alternatives depended on the streams of problems, policies and politics. It is concluded that some of the actors listed in the Plan are not part of the Multiple Streams Model and the existence of a distinct factor of this model demonstrated, guidelines and determinations of the Brazilian Ministry of Tourism, which influences the flow of public policies and politics.